Avaliação da região periimplantar por tomografias computadorizadas multislice e cone-beam - estudo in vitro - Branda, Fabrício Baú (2012)
The goal of this research was to verify the reproduction of details in the periimplant region in MultiSlice and CONE BEAM CT scans on in vitro studies, simulating five postoperative situations. Two assessments were applied: comparative quantitative analysis, of vertical measurement from the protein platform of dental implants to the first bone-implant contact and the thickness of this bone tissue from the first contact, between the sample and tomographic images of two CONE BEAM CT scanners and a MultiSlice CT scanner, with ANOVA statistical analysis (α=0.05); and qualitative analysis of reproduction accuracy of details from the tomographies performed by six experienced evaluators, with Kruskal-Wallis statistical analysis (α=0.05). For the quantitative assessment, there was no significant statistical difference only for Implant 1 (Control Group and CONE BEAM Kodak – A and B); Implant 2 (Control Group and CONE BEAM i-CAT for region A); Implant 4 (Control Group, CONE BEAM i-CAT and MultiSlice Siemens 128 channels for region B); Implant 5 (Control Group and MultiSlice Siemens 128 channels for region A). For the qualitative assessment, there was preference in three out of five situations studied for CONE BEAM CT scanners; in one there was a preference for MultiSlice, and in situation 5 there was no significant statistical difference among scanners. The formation of metallic artifacts was common to the scanners studied. Although no CT scanners have reproduced accurately all situations tested, there was a preference from the evaluators in the qualitative assessment for the images of the CONE-BEAM CT scanners